2018
DOI: 10.1128/jvi.01083-18
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Crimean-Congo Hemorrhagic Fever Virus-Induced Hepatic Injury Using Antibody-Mediated Type I Interferon Blockade in Mice

Abstract: Crimean-Congo hemorrhagic fever virus (CCHFV) can cause severe hepatic injury in humans. However, the mechanism(s) causing this damage is poorly characterized. CCHFV produces an acute disease, including liver damage, in mice lacking type I interferon (IFN-I) signaling due to either STAT-1 gene deletion or disruption of the IFN-I receptor 1 gene. Here, we explored CCHFV-induced liver pathogenesis in mice using an antibody to disrupt IFN-I signaling. When IFN-I blockade was induced within 24 h postexposure to CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 64 publications
4
74
0
1
Order By: Relevance
“…Largely, our findings were consistent with reports in other mouse models. We saw a peripheral blood lymphopenia correlating with increasing disease severity, similar to observations made in Stat-1 -/- [5] and Rag2 -/mice [10], and increases in plasma levels of pro-inflammatory cytokines (IL-6 and IL-18) and chemoattractants (CCL2, CXCL1, and CXCL10) reported in the C57BL/6J (BL6) IFN-1-blockade disease model [10]. We did, however, note some variation in intensity of cytokine level changes than those reported in other mice.…”
Section: Differential Cytokine Expression In Mice Infected With Eithesupporting
confidence: 85%
See 2 more Smart Citations
“…Largely, our findings were consistent with reports in other mouse models. We saw a peripheral blood lymphopenia correlating with increasing disease severity, similar to observations made in Stat-1 -/- [5] and Rag2 -/mice [10], and increases in plasma levels of pro-inflammatory cytokines (IL-6 and IL-18) and chemoattractants (CCL2, CXCL1, and CXCL10) reported in the C57BL/6J (BL6) IFN-1-blockade disease model [10]. We did, however, note some variation in intensity of cytokine level changes than those reported in other mice.…”
Section: Differential Cytokine Expression In Mice Infected With Eithesupporting
confidence: 85%
“…In animal models of disease, identifying immunological parallels with and divergences from human disease is critical to support applicability of the model and guide translational studies. In addition to Ifnar -/mice, Stat-1 -/- [5], Rag2 -/mice [10], and NSG-SGM3 humanized [8] mice have been reported to develop clinical signs following CCHFV infection. Ifnar -/mice are deficient in type I IFN signaling; Stat-1 -/mice are deficient in type I, type II, and type III signaling; Rag2 -/mice are unable to generate mature T or B lymphocytes; and humanized mice have a variety of potential alterations to the immune response based on deficiencies in the mouse background and humanization approach.…”
Section: Differential Cytokine Expression In Mice Infected With Eithementioning
confidence: 99%
See 1 more Smart Citation
“…Susceptibility to disease from CCHFV in mice has been limited to strains deficient in type I interferon responses [67,68]. These mice show a very rapid and highly lethal disease progression [69,70], which is likely largely due to their genetically defective antiviral response rather than a faithful recapitulation of human Crimean-Congo hemorrhagic fever (CCHF)-pathogenesis [70].…”
Section: Nairovirusesmentioning
confidence: 99%
“…These data suggest that host responses, although effective in controlling viral replication, may contribute to the severe tissue pathology seen in these mice. However, studies in mice deficient in adaptive immune responses demonstrated that mice could develop severe tissue pathology in the absence of cytolytic T-cell activity, suggesting this host response is dispensable for tissue damage following CCHFV infection (31). Further studies are needed to determine whether host responses to CCHFV infection contribute to the pathogenesis of CCHFV.…”
Section: Figmentioning
confidence: 99%